PENGARUH PARTISIPASI ANGGARAN DAN KETERLIBATAN KERJA TERHADAP SENJANGAN ANGGARAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING (Studi pada Aparat Pemerintah Daerah Kampung Wasur) - Caecilia Henny Setya Wati; Aprillia Katje Seilatuw (EKONOMI & SOSIAL, 2012)
The purpose of this study was to analyze the effect of organizational commitment as a moderating variable on the relationship between budgetary participation and budgetary slack and to analyze the influence of organizational commitment as a moderating variable on the relationship between job involvement with budgetary slack.     The sample in this study is the work unit specially selected local officials Wasur village on the grounds of this institution is government work units that make, use, and report the budget or as executing budgets of local governments.      The results of regression analysis of the first hypothesis suggests that the coefficient of the interaction between organizational commitment and participation in the budget for significant budgetary slack. The regression analysis on the second hypothesis suggests that the interaction coefficient of interaction between organizational commitment and job involvement significantly.